Flexible AMOLED Display and Gate‐driver with Self‐aligned IGZO TFT on Plastic Foil. Issue 1 (June 2014) - Nag, Manoj; Obata, Koji; Fukui, Yusuke; Myny, Kris; Schols, Sarah; Vicca, Peter; Ke, Tung Huei; Smout, Steve; Willegems, Myriam; Ameys, Marc; Bhoolokam, Ajay; Muller, Robert; et al.
Abstract We present a QQVGA (160times120 with 3 sub‐pixel) top‐emitting AMOLED display with 85ppi resolution using a self‐aligned (SA) IGZO TFT backplane on polyimide‐foil. The back plane process flow is based on a 5 layer photolithography process. The aperture ratio of the top‐emitting OLEDs is approx. 25%. For operation at 6 V supply voltage (VDD), the brightness of the display exceeds 150cd/m2. On the same substrate a 160 stage gate‐driver was measured at FHD rate.